DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DA ATIVIDADE ANTIOXIDANTE DE NANOPARTÍCULAS CONTENDO APOCININA - Souza, Bianca Ferreira de (2021)
Apocynin is extracted from the root of the medicinal plant Picrohiza kurroa, and despite its wide potential, apocynin has pharmacokinetic limitations, such as low oral bioavailability and rapid elimination, close dose-response relationship, thus limiting its clinical application. Several studies have established that the beneficial properties of apocynin are related to the demonstrated antioxidant activity, however there are limitations due to its pharmacokinetic properties. The use of knowledge from nanotechnology offers therapeutic opportunities for agents that are used with little efficacy in oral formulations, mainly due to their low bioavailability, such as apocynin. In this sense, the present work proposes the realization of nanoparticles containing this drug to maximize its use. For its realization, the methodology used was coacervation, for the production of nanoparticles containing apocynin, they were still coated with polysorbate 80 (0.75% w/v). Linearity was evaluated with the aid of an ultraviolet spectrophotometer, where the graph formulation was obtained, in addition to the straight line equation. To assess the average diameter, the light scattering technique was used. The nanoparticles obtained had an average diameter of 194 nm, an encapsulation efficiency of 74% and a polydispersion index of less than 0.3. The use of polysorbate 80 (Tween 80) as a coating proved to be adequate in the formulation with 0.75% w/v, where the average diameter was 208,99 nm and polydispersion index of 0.108, however, statistically not there was a significant difference. For characterization, DRX (X-Ray Diffraction) and FT-IR (Infrared Spectrometer) were performed, where the presence of the inputs used in the preparation of the nanoparticles can be elucidated. By the Scanning Electron Microscopy technique it was possible to observe the morphology and the presence of particles formed by albumin (BSA), apocynin (APO) and polysorbate 80 (PS80). The antioxidant analysis was performed using the DPPH test. In the DPPH assay it was observed that the nanoparticles produced a lower percentage of inhibition than ascorbic acid With the data obtained in this experiment, it can be said that the nanoparticles were successfully obtained, giving future in vitro and in vivo tests as a perspective to verify their effectiveness.